2020
DOI: 10.24198/cropsaver.v3i2.31305
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of the extracts of Piper retrofractum fruit and Tephrosia vogelii leaf and their mixtures against Crocidolomia pavonana

Abstract: This laboratory work was carried out to evaluate the insecticidal activity of the extracts of Piper retrofractum (Piperaceae) fruit and Tephrosia vogelii (Fabaceae) leaf and their mixtures against the cabbage head caterpillar, Crocidolomia pavonana. Ground plant materials of the two plant species were extracted separately with n-hexane and methanol. The results of leaf-residue feeding bioassays showed that P. retrofractum (Pr) and T. vogelii (Tv) hexane extracts had strong insecticidal activity against C. pavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Pests control efforts can be carried out with more environmentally friendly pesticides such as using botanical and microbial insecticides. Most of the studies that have been conducted have tested the effectiveness of botanical insecticides [4,[6][7][8]. Another alternative in controlling insect pests is the use of microbes as pest control agents.…”
Section: Introductionmentioning
confidence: 99%
“…Pests control efforts can be carried out with more environmentally friendly pesticides such as using botanical and microbial insecticides. Most of the studies that have been conducted have tested the effectiveness of botanical insecticides [4,[6][7][8]. Another alternative in controlling insect pests is the use of microbes as pest control agents.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are major constituents of well-known substances including botanical insecticides, deterrents, and repellents that may be useful for controlling a wide range of pests ( Isman, 2006 ). Research has been performed regarding the effectiveness of hexane extract from long pepper fruit in controlling different insect pests such as cabbage head caterpillar larvae ( Prijono et al., 2020 ), tobacco cutworm larvae ( Ratwatthananon et al., 2020 ), and southern house mosquito larvae ( Wiwattanawanichakun et al., 2018 ). These reports also showed that by using hexane solvent, the long pepper fruit extract presented higher effectiveness against insects than other solvents such as dichloromethane, ethyl acetate, methanol, and ethanol.…”
Section: Introductionmentioning
confidence: 99%